Crystal structure, thermal behavior and vibrational studies of tetraethylammonium dihydrogenarsenate bis-arsenic acid [(C2H5)4N].[H2AsO4].[H3AsO4]2 - Dhouib, Ikram; Guionneau, Philippe; Mhiri, Tahar; Elaoud, Zakaria (European Journal of Chemistry, 2014)
An organic-inorganic hybrid compound of tetraethylammonium dihydrogenarsenate bis-arsenic acid salts of formula [(CH3CH2)4N].[H2AsO4].[H3AsO4]2(TEAs) were grown by the slow evaporation and characterized by means of single crystal X-ray diffraction, thermal analysis, FT-IR and Raman spectroscopy. This compound crystallize in the space groups Cc with unit cell parameters, a= 20.105(2) Å; b= 7.342(4) Å, c = 15.292(2) Å, γ = 115(4)°, Z = 4, R= 0.07. The structure has solved using direct methods and refined by least-squares analysis. In this case, the structure consists of infinite parallel two-dimensional planes built of mutually H2AsO4−, H3AsO4 tetrahedra connected by strong O-H···O hydrogen bonding. The thermoanalytical properties were studied using TG of TEAs method in the temperature ranges from 300 to 440 K for this hygroscopic sample. DSC measurement was carried out in the temperature range from 305 to 425 K.